Associations in the continuum of care for maternal, newborn and child health: a population-based study of 12 sub-Saharan Africa countries. (December 2016) - Owili, Patrick; Muga, Miriam; Chou, Yiing-Jenq; Hsu, Yi-Hsin; Huang, Nicole; Chien, Li-Yin
Abstract Background Despite the progress in the Millennium Development Goals (MDGs) 4 and 5, inequity in the utilization of maternal, newborn and child health (MNCH) care services still remain high in sub-Saharan Africa (SSA). The continuum of care for MNCH that recognizes a tight inter-relationship between maternal, newborn and child health at different time periods and location is key towards reducing inequity in health. In this study, we explored the distributions in the utilization MNCH services in 12 SSA countries and further investigated the associations in the continuum of care for MNCH. Methods Using Demographic and Health Surveys data of 12 countries in SSA, structural equation modeling approach was employed to analyze the complex relationships in continuum of care for MNCH model. The Full Information Maximum Likelihood estimation procedure which account for the Missing at Random (MAR) and Missing Completely at Random (MCAR) assumptions was adopted in LISREL 8.80. The distribution of MNCH care utilization was presented before the estimated association in the continuum of care for MNCH model. Results Some countries have a consistently low (Mali, Nigeria, DR Congo and Rwanda) or high (Namibia, Senegal, Gambia and Liberia) utilization in at least two levels of MNCH care. The path relationships in the continuum of care for MNCH from 'adequate antenatal care' to 'adequate delivery care' (0.32) and to 'adequate child's immunization' (0.36); from 'adequate delivery care' to 'adequate postnatal care' (0.78) and to 'adequate child's immunization' (0.15) were positively associated and statistically significant atp  < 0.001. Only the path relationship from 'adequate postnatal care' to 'adequate child's immunization' (−0.02) was negatively associated and significant atp  < 0.001. Conclusions In conclusion, utilization of each level of MNCH care is related to the next level of care, that is – antenatal care is associated with delivery care which is then associated with postnatal and subsequently with child's immunization program. At the national level, identification of communities which are greatly contributing to overall disparity in health and a well laid out follow-up mechanism from pregnancy through to child's immunization program could serve towards improving maternal and infant health outcomes and equity.